Comparatively Thermal and Crystalline Study of Poly(methyl‐methacrylate)/Polyacrylonitrile Hybrids: Core–Shell Hollow Fibers, Porous Fibers, and Thin Films. Issue 11 (10th June 2016) - Huang, Jiangnan; Cao, Yonghai; Huang, Zhongyuan; Imbraguglio, Samantha A.; Wang, Zhe; Peng, Xiangfang; Guo, Zhanhu
Abstract : Porous fibers, core–shell hollow fibers, and porous thin films are prepared from polyacrylonitrile/poly(methyl methacrylate) by coaxial electrospinning, single electrospinning, and spin‐coating technologies, respectively. Thermal stability and crystalline properties are comparatively studied for the products from different processes. Abstract : The polyacrylonitrile/polymethyl‐methacrylate (PMMA/PAN) porous fibers, core–shell hollow fibers, and porous thin films are prepared by coaxial electrospinning, single electrospinning, and spin‐coating technologies, respectively. The different morphologies arising from different processes display great influences on their thermal and crystalline properties. The adding of PMMA causes porous structure due to the microphase‐separation structure of immiscible PMMA and PAN phases. The lower weight loss, higher degradation temperature, and glass‐transition temperatures of porous thin films than those of porous fibers and core–shell hollow fibers are obtained, evidencing that the polymer morphologies produced from the different process can efficiently influence their physical properties. The orthorhombic structure of PAN crystals are found in the PMMA/PAN porous thin films, but the rotational disorder PAN crystals due to intermolecular packing are observed in the PMMA/PAN porous fibers and core–shell hollow fibers, indicating that different processes cause different types of PAN crystals.